A multilevel intervention to increase physical activity and improve healthy eating and physical literacy among young children (ages 3-5) attending early childcare centres: the Healthy Start-Départ Santé cluster randomised controlled trial study protocol. (December 2016) - Bélanger, Mathieu; Humbert, Louise; Vatanparast, Hassan; Ward, Stéphanie; Muhajarine, Nazeem; Chow, Amanda; Engler-Stringer, Rachel; Donovan, Denise; Carrier, Natalie; Leis, Anne
Abstract Background Childhood obesity is a growing concern for public health. Given a majority of children in many countries spend approximately 30 h per week in early childcare centers, this environment represents a promising setting for implementing strategies to foster healthy behaviours for preventing and controlling childhood obesity. Healthy Start-Départ Santé was designed to promote physical activity, physical literacy, and healthy eating among preschoolers. The objectives of this study are to assess the effectiveness of the Healthy Start-Départ Santé intervention in improving physical activity levels, physical literacy, and healthy eating among preschoolers attending early childcare centers. Methods/Design This study follows a cluster randomized controlled trial design in which the childcare centers are randomly assigned to receive the intervention or serve as usual care controls. The Healthy Start-Départ Santé intervention is comprised of interlinked components aiming to enable families and educators to integrate physical activity and healthy eating in the daily lives of young children by influencing factors at the intrapersonal, interpersonal, organizational, community, physical environment and policy levels. The intervention period, spanning 6-8 months, is preceded and followed by data collections. Participants are recruited from 61 childcare centers in two Canadian provinces, New Brunswick and Saskatchewan. Centers eligible for this study have to prepare and provide meals for lunch and have at least 20 children between the ages of 3 and 5. Centers are excluded if they have previously received a physical activity or nutrition promoting intervention. Eligible centers are stratified by province, geographical location (urban or rural) and language (English or French), then recruited and randomized using a one to one protocol for each stratum. Data collection is ongoing. The primary study outcomes are assessed using accelerometers (physical activity levels), the Test of Gross Motor Development-II (physical literacy), and digital photography-assisted weighted plate waste (food intake). Discussion The multifaceted approach of Healthy Start-Départ Santé positions it well to improve the physical literacy and both dietary and physical activity behaviors of children attending early childcare centers. The results of this study will be of relevance given the overwhelming prevalence of overweight and obesity in children worldwide. Trial registration NCT02375490 (ClinicalTrials.gov registry).